Efficacy of pyriproxyfen-pyrethroid long-lasting insecticidal nets (LLINs) and chlorfenapyr-pyrethroid LLINs compared with pyrethroid-only LLINs for malaria control in Benin: a cluster-randomised, superiority trial. Issue 10375 (11th February 2023) - Accrombessi, Manfred; Cook, Jackie; Dangbenon, Edouard; Yovogan, Boulais; Akpovi, Hilaire; Sovi, Arthur; Adoha, Constantin; Assongba, Landry; Sidick, Aboubacar; Akinro, Bruno; Ossè, Razaki; Tokponnon, Filémon; et al.
Summary: Background: New classes of long-lasting insecticidal nets (LLINs) combining mixtures of insecticides with different modes of action could put malaria control back on track after rebounds in transmission across sub-Saharan Africa. We evaluated the relative efficacy of pyriproxyfen-pyrethroid LLINs and chlorfenapyr-pyrethroid LLINs compared with standard LLINs against malaria transmission in an area of high pyrethroid resistance in Benin. Methods: We conducted a cluster-randomised, superiority trial in Zou Department, Benin. Clusters were villages or groups of villages with a minimum of 100 houses. We used restricted randomisation to randomly assign 60 clusters to one of three LLIN groups (1:1:1): to receive nets containing either pyriproxyfen and alpha-cypermethrin (pyrethroid), chlorfenapyr and alpha-cypermethrin, or alpha-cypermethrin only (reference). Households received one LLIN for every two people. The field team, laboratory staff, analyses team, and community members were masked to the group allocation. The primary outcome was malaria case incidence measured over 2 years after net distribution in a cohort of children aged 6 months–10 years, in the intention-to-treat population. This study is ongoing and is registered with ClinicalTrials.gov, NCT03931473 . Findings: Between May 23 and June 24, 2019, 53 854 households and 216 289 inhabitants were accounted for in the initial census and included in the study. Between March 19 and 22, 2020, 115 323 LLINs were distributed to 54 030 households in an updated census. A cross-sectional survey showed that study LLIN usage was highest at 9 months after distribution (5532 [76·8%] of 7206 participants), but decreased by 24 months (4032 [60·6%] of 6654). Mean malaria incidence over 2 years after LLIN distribution was 1·03 cases per child-year (95% CI 0·96–1·09) in the pyrethroid-only LLIN reference group, 0·84 cases per child-year (0·78–0·90) in the pyriproxyfen-pyrethroid LLIN group (hazard ratio [HR] 0·86, 95% CI 0·65–1·14; p=0·28), and 0·56 cases per child-year (0·51–0·61) in the chlorfenapyr-pyrethroid LLIN group (HR 0·54, 95% CI 0·42–0·70; p<0·0001). Interpretation: Over 2 years, chlorfenapyr-pyrethroid LLINs provided greater protection from malaria than pyrethroid-only LLINs in an area with pyrethroid-resistant mosquitoes. Pyriproxyfen-pyrethroid LLINs conferred protection similar to pyrethroid-only LLINs. These findings provide crucial second-trial evidence to enable WHO to make policy recommendations on these new LLIN classes. This study confirms the importance of chlorfenapyr as an LLIN treatment to control malaria in areas with pyrethroid-resistant vectors. However, an arsenal of new active ingredients is required for successful long-term resistance management, and additional innovations, including pyriproxyfen, need to be further investigated for effective vector control strategies. Funding: UNITAID, The Global Fund.